The Development of Self-Direction and Self-Regulation Skills to Improve the Effectiveness of Learning of High School Students - Suherman, Suherman (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
In the 21st century, life is packed with challenges and the search for identity in an adolescent developmental phase; high school students are faced with the demands of a constantly changing environment, open and diverse opportunities and choices, and increasingly fierce competition. Therefore, students need to have self-direction and self-regulation skills to live their lives effectively and face their future in a more directed manner. Students with inadequate self-direction and self-regulation skills can encounter many problems and developmental experience confusion, indecision, and immaturity. This study aims to discover guidance and counseling strategies to help young students develop self-direction and self-regulation skills to undergo the learning process more effectively and independently. The research and development method was used. The respondents were ten school counselors and 643 high school students in the West Java Province of Indonesia. Research produces Self-Direction and Self-Regulation Skills Development Guidelines for High School Students. These guidelines are proven effective in fostering students’ self-direction and self-regulation skills, which include: initiative, autonomy, self-regulation, and responsibility.Keywords:  adolescence; a time of crisis; self-direction skills; effective learning process Di abad 21, kehidupan penuh dengan tantangan dan pencarian jati diri dalam fase perkembangan remaja; Siswa SMA dihadapkan pada tuntutan lingkungan yang terus berubah, peluang dan pilihan yang terbuka dan beragam, serta persaingan yang semakin ketat. Oleh karena itu, siswa perlu memiliki keterampilan mengarahkan diri dan mengatur diri sendiri untuk menjalani kehidupannya secara efektif dan menghadapi masa depan mereka secara lebih terarah. Siswa dengan pengarahan diri dan keterampilan pengaturan diri yang tidak memadai dapat menghadapi banyak masalah dan mengalami kebingungan, keragu-raguan, dan ketidakdewasaan perkembangan. Penelitian ini bertujuan untuk menemukan strategi bimbingan dan konseling untuk membantu siswa muda mengembangkan keterampilan pengarahan diri dan pengaturan diri untuk menjalani proses pembelajaran secara lebih efektif dan mandiri. Metode penelitian dan pengembangan yang digunakan. Respondennya adalah sepuluh guru BK dan 643 siswa SMA di Provinsi Jawa Barat, Indonesia. Penelitian menghasilkan Pedoman Pengembangan Keterampilan Self-Direction dan Self-Regulation untuk Siswa SMA. Pedoman ini terbukti efektif dalam membina keterampilan mengarahkan dan mengatur diri siswa, yang meliputi: inisiatif, otonomi, pengaturan diri, dan tanggung jawab.Kata kunci: masa remaja; saat krisis; self-direction skills; proses belajar yang efektif